The impacts of roughness length on the simulation of land-atmosphere water and heat exchanges over the Yarlung Zangbo Grand canyon region - Zhang, Qiang; Wen, Jun; Zhang, Tangtang; Yang, Yiting; Wu, Yueyue; Zhang, Ge; Liu, Wenhui; Chen, Yaling; Yan, Zhitao (Frontiers in Earth Science, 2023)
Precipitation has a significant influence on the topsoil moisture and further impacts the land-atmospheric water and heat exchange process over the Yarlung Zangbo Grand Canyon region (YGC). The simulated performance of CLM5.0 on turbulent fluxes under seven roughness heights for heat transfer (Z0h) schemes at Motuo and Pailong stations in this region in this study. The results indicate that the Community Land Model version 5.0 (CLM5.0) significantly overestimates the surface sensible heat flux (H) while the simulation performance of surface latent heat flux (LE) is better than H. By comparing and analyzing the simulation results, the Z0h schemes suitable for the YGC are selected optimally. The Zeng et al. (2012) scheme (Z12) is more suitable for the simulations of H, with the simulated RMSE of H at Motuo and Pailong stations on typical sunny days being only 21.63 and 15.13 W∙m-2, respectively, 81.51% and 76.96% lower than the original Z0h scheme of CLM5.0. The Garratt (1978) scheme (G78) is more suitable for simulating LE in the YGC. The simulated BIAS and RMSE of LE at Motuo station were 9.80% and 21.90% lower than that under the default scheme of CLM5.0 on typical cloudy days. In addition, except for the G78 and CLM5.0 default scheme, the Z0h under the other schemes showed obvious diurnal variation characteristics, and H was positively sensitive to Z0h, while LE was the opposite. Consequently, the optimal Z0h schemes are of great application value for further comparative analysis of the water and heat exchange process between the Grand Canyon land surface and the atmosphere.